The Construction of Women As The Loving Subject In Curtis Sittenfield's Eligible - Asri, Zietha Arlamanda (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2023)
Women's presence as the dominant figure in the construction of patriarchal society is an emerging issue presented by Curtis Sittenfeld in her Novels. Liz is one of the female characters Curtis Sittenfeld displays in her novel Eligible. This figure of women who appear in her novel is very complex with many various dynamics. This study aims to examine the female main character as a loving subject in a male-dominated society. Applying Giddens's theory of loving subjects, the study's results revealed that Liz is described as the loving subject who seeks to build an intimate relationship with the man who became her choice. Through her behaviour and appearance, she was described as a loving subject who has a smooth character, sensitive and romantic. Liz is also shown as a private autonomous and has humanist and psychological dimensions, which are very complex inside. Curtis Sittenfeld as a writer presents the presence of women as the loving subject in a relationship of intimacy that is liquid and unrestricted. In this research, women are presented as an autonomous entity that has the same rights in a male-dominated society.